Optimization on Space Utilization in Penjaringansari Flats Surabaya - Syaifuddin Zuhri (Future Science)
Residential Housing are the current solution in the provision of houses for urban communities, especially for people who have limited ability in home ownership. A vertical housing is a collection of residential units are arranged vertically with a limited area, such as type 18 m2 up to 36m2. Residential units of towers usually consist of a space without borders with a bathroom or no bathroom inside, as well as a back porch for a clothes line or other service functions. Unrestricted residential units allow the occurrence of uncontrolled spaces of function or the occurrence of spaces that are multi-function and interfere with comfort or privacy, even increasing in line with the development of occupant characteristics. Optimal spatial arrangement is expected to realize harmony between humans, activities and built environment so that it does not create impact when utilization. And space actually shows the functional expressions that determine where the form should be found (Lutfiah, 2010), Space is something objective or real and subjective as the result of the human mind. This research is done by descriptive exploratory method (Marpaung, 2010) to know the background of the formation of a space that occurs after the residential process takes place. From these results will be able to determine what types of space is needed and often occurs in a development of residential apartment. So that later can be made guidance needs of the early space adaptive to the needs of residents towers.